2017
DOI: 10.1130/g39693.1
|View full text |Cite
|
Sign up to set email alerts
|

New U-Pb dates show a Paleogene origin for the modern Asian biodiversity hot spots

Abstract: Yunnan, in southwestern China, straddles two of the world's most important biodiversity hot spots (i.e., a biogeographic region that is both a reservoir of biodiversity and threatened with destruction) and hosts more than 200 fossiliferous sedimentary basins documenting the evolutionary history of that biodiversity, monsoon development, and regional elevation changes. The fossil biotas appear modern and have been assumed to be mostly Miocene in age. Dating has been by cross-correlation using palynology, magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 22 publications
(35 reference statements)
5
61
0
2
Order By: Relevance
“…We assume that the feldspar age most closely reflects the date of ash deposition and matches that of the youngest biotite. Step heating of a feldspar from ash Layer 11 gave a similar age of 33.32 ± 0.36 Ma, which is indistinguishable from that of ash Layer 3 when uncertainties are taken into account and suggests that the bottom part of the Lühe mine section was deposited at ~33 Ma, which is the same as U‐Pb ages (33 ± 1 Ma) from zircons in primary ashes exposed ~2.6 km to the southeast in Lühe town (Linnemann et al, 2018; see Figure 3 for location).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…We assume that the feldspar age most closely reflects the date of ash deposition and matches that of the youngest biotite. Step heating of a feldspar from ash Layer 11 gave a similar age of 33.32 ± 0.36 Ma, which is indistinguishable from that of ash Layer 3 when uncertainties are taken into account and suggests that the bottom part of the Lühe mine section was deposited at ~33 Ma, which is the same as U‐Pb ages (33 ± 1 Ma) from zircons in primary ashes exposed ~2.6 km to the southeast in Lühe town (Linnemann et al, 2018; see Figure 3 for location).…”
Section: Resultsmentioning
confidence: 79%
“…These paleoclimate proxy data were also used to reconstruct the paleoelevation of the Lühe area, which suggested an elevation of ~1 ± 0.8 km in the late Miocene (Hoke et al, 2014). However, Linnemann et al (2018) reported a 33–32 Ma U‐Pb zircon age of a primary volcanic ash within the plant‐bearing sediments from the southern tip of the Lühe Basin (Lühe town section; see Figure 3 for location). This new age, together with updated ages from the Jianchuan Basin (Gourbet et al, 2017), is significantly transforming our view about the tectonics, paleoclimate, and biodiversity of the SE margin of the Tibetan Plateau (Hoke, 2018; Linnemann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, sedimentary basins of the southeastern margin of the Tibetan Plateau have finally begun to yield absolute age constraints, including two new ages from volcanic ashes in the Lühe Basin reported in this issue of Geology (p. 3-6) by Linnemann et al (2017). This spate of geochronology (Hoke et al 2014;Gourbet et al 2017;Linnemann et al, 2017) squarely reassigns the age of at least two basins from middle and late Miocene to the Paleogene (Fig.…”
mentioning
confidence: 79%
“…Because Cenozoic continental sediments are difficult to date, the difference between the assumed and revised depositional age in SE Tibet can reach more than 20 m.y. (Gourbet et al, 2017;Linnemann et al, 2018). As a consequence, we cannot estimate an incision rate based on the age of the red beds, and so we simply used the observed range of 0.5-1.2 km as an estimate for the total incision since deposition.…”
Section: Sedimentology and Paleolandscapementioning
confidence: 99%